Research-based Instruction, an Essential Tenet of the Foreign Languages Pre-service-Teacher Education at Universidad de Pamplona - Cote-Parra, Gabriel (GIST – Education and Learning Research Journal, 2020)
This paper reports a personal reflection that describes how the Bachelor of Arts in Foreign Languages at the Universidad de Pamplona provides preservice teachers with a research-based instruction. In an attempt to contribute to today’s scholar discussions on foreign language pre-service teachers’ education, this reflective piece illustrates a unique way of teaching research to FL undergraduates. The author first provides an overview on the area of teaching research to undergraduates in Colombia; second, a description of how pre-service teachers learn the theoretical foundations, paradigms, designs and approaches mostly used in educational inquiry; and the two-year process student researchers go through. Finally, the author discusses the lessons learned and what the future of this process might be like.